DAGHESTAN AND TATARSTAN: THE STATE/RELIGION RELATIONSHIP IN THE ISLAMIC CONTEXT OF RUSSIA - ABDULAGATOV, Zaid (CENTRAL ASIA AND THE CAUCASUS, 2005)
For my analysis of the relations between Islam and the state in Russia I have selected Daghestan and Tatarstan, two republics with predominantly Muslim populations which demonstrate the two most typical patterns of such relations. Islam in Daghestan has concentrated the main features of this religion in the Northern Caucasus, home of about 4.5 million Muslims, over 40 percent of whom belong to the Daghestanian ethnic groups. Islam in Daghestan has a common history with Islam in the neighboring republics. This is   best illustrated by the Caucasian War of the 1820s-1850s and by the Soviet period (mainly between May 1944 and January 1990 when all religious organizations in the region were supervised by the Spiritual Administration of the Muslims of the Northern Caucasus). Today, the local religious organizations are working in close contact with the Coordinating Center of the North Caucasian Muslims (CCNCM), which has several co-chairmen who alternate once every three years. The fact that the Daghestanian ethnoses share many of the adats (all sorts of taboos, blood feud sworn brotherhood, hospitality, etc.) makes the republic best suited for the purposes of my analysis. It is equally important that in Daghestan and its neighbors, the Sunni Shafi‘i madhab is the most widespread. In addition, Daghestan and other North Caucasian republics have been most exposed to the problems created by Islamic extremism. Daghestan was the first among them to pass the so-called anti-Wahhabi law in September 1999. Kabardino-Balkaria, Karachaevo-Cherkessia, and Ingushetia followed suit; Wahhabism was also banned in Chechnia.1The above shows that for many reasons Daghestan can be regarded as a “model of the Northern Caucasus.” As distinct from Tatarstan, Islam in Daghestan is functioning under difficult socioeconomic conditions, which are especially obvious high in the mountains and in the foothills. Specialists in social sciences and experts on the Caucasus are of the opinion that the traditions of the Daghestanian mountain peoples are dying away as remnants of patriarchal and semi-patriarchal societies.